A Case Study on Utilising Soy and Whey Protein Polymers: Advances in Enteric Coatings for Improved Delayed-Release Pharmaceuticals - Enas Bshena; Abdalrahem Shtawa; Sarra Takita; Magdi Mussa (Chemistry Proceedings, 2024)
An enteric coating plays a crucial role in preventing the disintegration of pharmaceutical dosage forms in the stomach. This is particularly important for drugs unstable at an acidic pH or designed to act in the small intestine. While conventional synthetic polymers have been widely used for enteric coatings, there is growing interest in exploring naturally derived proteins as an alternative. This study focused on two natural polymers: soy protein and whey protein isolates, first by determining the gastro-resistance properties of films prepared from these proteins. Then, appropriate casting solutions were developed to create polymeric films, and their resistance to acidic pH was evaluated using disintegration tests. Second, crate drug pellets coated with the most effective protein-based film were previously prepared, and their performance was assessed using the USP apparatus I (basket). The results demonstrated that the coated pellets (SA and SAG) exhibited excellent gastro-resistance properties. Specifically, the percentage release of the coated pellets met the USP criteria: less than 10% release in the first 2 h under acidic conditions, followed by at least 80% release within 45 min in the buffer phase. In contrast, uncoated pellets showed immediate release, with over 69% of the dye released during the initial 2 h. Notably, the SA and SAG-coated pellets demonstrated remarkable resistance to acidic pH, releasing only 1% and approximately 2% of the dye faster than uncoated pellets. These findings highlight the potential of SA and SAG coating films for efficient delayed release or enteric coating applications.